PENGARUH KEADILAN DISTRIBUTIF, INTERAKSIONAL DAN PROSEDURAL TERHADAP BUDGETARY SLACK HOTEL BINTANG LIMA DI BADUNG - Wahyuni, Ni Luh Eka; Asana, Gde Herry Sugiarto; Oktaviani, Laras (Universitas Triatma Mulya, 2024)
Based on the profit and loss report for Hotel The report also shows that budgeted expenses are higher than income, this can also trigger budgetary slack. There are several factors that influence budgetary slack, one of which is the dimension of justicei which consistss of idistributive ijustice, interactonal justice, procedur justice where if this dimension of justice is implemented well and appropriately it will reduces the occurrences of budgetary slack. The aim of this research is to determin and analyse: (1) the influence of distributive justice on budgetary slack; (2) the influence of interactional justice on budgetary slack; (3) the influence of procedural justice on budgetary slack. The sort of examination is quantitative exploration. 158 employees participated in this study's survey. Primari data are the kind of data used. The questionnaires is used for data collection. Multiple linear regression is the method used in the data analysis. The results of the research conclude that distributive justice, interactional justice n procedural justice have a significant effect on budgetary slack in five star hotels in Badung. Based on the regression coefficient value obtained, it is negative, indicating that there is a negative influence between the variables of distributive justice, interactional justice n proceduraly justicei on budgetarys slack in five star hotels in Badung. The extent of the influence of the variables distributive justice, interactional justice, and procedural justice on Budgetary Slack is 25.5%, and 74.5% is influencei by factorss outsidei of this studys.